Ethnicity and Voting Behavior in the Ashanti and Volta Regions of Ghana: A Cramp in the Wheel of a Fledgling Democracy? - Joseph Kingsley Adjei (Journal of Global Initiatives, 2013)
This paper discusses the substance and potential impact of ethnic block voting in two of Ghana's 10 political regions: Ashanti and Volta. Using the Electoral Commission of Ghana's dataset for five Presidential election results from 1992 to 2008, the paper confirms ethnic block voting in the two regions. The paper views the phenomenon as detrimental to Ghana's evolving democracy as it is a potential trigger for civil war, and recommends vigorous education, equitable distribution of resources, and comprehensive development to curb the problem.